Sphingolipids in Neurodegeneration - Haughey, Norman J. (2010)
Although the brain contains a high content of sphingolipids, we know relatively little about the roles that sphingolipids play in regulating neural functions. Once regarded only for their structural roles in maintaining the integrity of cellular and sub-cellular compartments, it is now apparent that many sphingolipid species are biologically active and play important roles in regulating signaling events. Recent technological and scientific advances are rapidly increasing our knowledge of the roles that sphingolipids play in regulating normal neural activity. Likewise, we are beginning to understand how perturbations in sphingolipid metabolism contribute to the pathogenesis of a variety of neurodegenerative conditions. In this special issue of NeuroMolecular Medicine, we present a series of review articles that summarize new and emerging technologies for the analysis of sphingolipids, sphingolipid metabolic pathways, and how dysfunctions in sphingolipid metabolism contribute to neurodegeneration in lysosomal storage disorders, Alzheimer’s disease and Multiple Sclerosis.